Evaluation of Waiting Time and Satisfaction in Outpatients in Imam Hossein Polyclinic of Zanjan Using Patient-Pathway Analysis - Roya Jalili; Mehdi Mohebbi; Saeid Asefzadeh; Mahnaz Mohebbi (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Waiting time is an important factor affecting the satisfaction of outpatients and also one of the indicators for assessing the level of access to health care services as well as service quality. Objectives: The aim of this study was to evaluate the waiting time and satisfaction in outpatients referring to Imam Hossein polyclinic, Zanjan in 2017 using patient flow analysis (PFA). Methods: The present research is a descriptive-analytical study. A total of 392 outpatients were selected using a convenience sampling method. Data were collected using a timing checklist and Patient Satisfaction Questionnaire (PSQ) and analyzed using structural equation analysis and analysis of variance through LISREL 8.5, MINITAB 17.2, SPSS 24, and STATISTICA 12 software. Results: According to the obtained data, the longest average waiting time was in the radiology clinic (27±11 minutes), and the shortest was in the pharmacy (5±3 minutes). Also, the average duration of the examination was 9±9 minutes. The mean patient satisfaction was 3.38 out of 5 (average degree of satisfaction). The results showed that waiting time was inversely related to patient satisfaction and examination time was directly related to satisfaction, and waiting time in the laboratory and admission had the greatest effect on reducing patient satisfaction. Also, the patientchr('39')s waiting time to receive services and the duration of the doctorchr('39')s visit were at an acceptable level and patientschr('39') satisfaction with the waiting time was at a moderate level. Conclusion: Since the radiology clinic was one of the bottlenecks of outpatient facilities in this polyclinic, measures to reduce waiting time and increase patient satisfaction are recommended.